Development of muscle mass: How much is optimum for performance?. - Young, W.; Talpey, S.; Bartlett, R.; Lewis, M.; Mundy, S.; Smyth, A.; Welsh, T. (Strength and Conditioning Journal, 2019)
Training for muscle hypertrophy can be expected to induce some increase in total body mass, and this can have positive or negative consequences for athletic performance. Positive effects may be increased strength, increased resistance to being pushed aside, and greater momentum when running, whereas possible negative effects may be reduced capacity to accelerate, decelerate, change direction, and jump. These possible effects of gaining muscle and total body mass suggest that strength and conditioning coaches should give thoughtful consideration to the amount of hypertrophy training prescribed throughout an athlete's development and should be determined by the specific needs of the athlete.